Improvement in Performance across the Supply Chain by Market Strategic Alignment in the Textile Sector of Indonesia - Rehning Kurnia; Warsono Warsono; Erny Roesminingsih; Sugi Hartono (International Journal of Supply Chain Management, 2020)
Abstract-Recently, supply chain practices are consider are the effective practices because it enhance he business performance by improving their processes and also capture the emphasis of the researchers. Thus, the ongoing study’s aim is to inspect the role of market strategies and market performance along with the supply chain performance on the firm performance of the textile sector in Indonesia. The examination of mediation role of supply chain performance among the links of market strategies, market performance and firm performance. The workers of marketing along with the supply chain department are the respondents and data were extracted from them by questionnaires that was analyzed by PLS-SEM. The findings indicated that market strategies and market performance have positive impact on the firm performance while the outcomes also elaborated that supply chain performance has positive mediation among the nexus of market strategies, market performance and firm performance. These findings give the insight to the regulators that they should improve their emphasis towards the supply chain and marketing performance that enhance the firm performance of the industry.